Automatic Measurement of LED Colorimetric Parameters Based on LabVIEW - 林卫国 刘依 杨明忠 (东华大学学报（英文版）, 2011)
In order to accurately and automatically measure the light emitting diode（LED） colorimetric parameters,the design of a measurement system by adopting a high-performance spectrometer and looking-up table method was presented based on the LabVIEW.First,the data of the LED relative spectral power distribution（SPD） were read by the spectrometer to measure LED chromaticity coordinate,and the slopes table were formed by the LED chromaticity coordinate and the equal stimulus point.Then,the CIE1931 chromaticity diagram was divided into 4 different regions to ensure the slopes table that had the character of monotonic decreasing.Finally,the LED dominant wavelength and purity were automatically calculated using the LabVIEW programs.The data of LEDs＇ colorimetric parameters have demonstrated that the measurement method in this paper can achieve higher precision result.